Maternal Pre‐pregnancy Body Mass Index and Gestational Weight Gain in Relation to Autism Spectrum Disorder and other Developmental Disorders in Offspring. Issue 2 (21st December 2018) - Windham, Gayle C.; Anderson, Meredith; Lyall, Kristen; Daniels, Julie L.; Kral, Tanja V.E.; Croen, Lisa A.; Levy, Susan E.; Bradley, Chyrise B.; Cordero, Christina; Young, Lisa; Schieve, Laura A.
Abstract : Most prior studies examining maternal pre‐pregnancy body mass index (BMI) in relation to offspring autism spectrum disorders (ASD) have reported an association, though findings are not uniform and few have also examined gestational weight gain (GWG). Therefore, we examined both in the Study to Explore Early Development, a multi‐site case–control study of children born in 2003–2006. Children identified from clinics, schools, and birth certificates were enrolled at ages 2–5 year and using standardized developmental evaluations, classified as: ASD, other developmental delays (DD), or population‐based controls. Maternal height, weight, and GWG were self‐reported during the telephone interview. Three primary weight risk factors were examined: (a) Pre‐pregnancy BMI, classified as underweight to obese, (b) GWG continuous and categorized as quintiles, and (c) Institute of Medicine clinical weight‐gain recommendations. Odds ratios adjusted (AOR) for sociodemographic and prenatal factors were calculated among term singletons, comparing the ASD ( n = 540) or DD ( n = 720) groups to the control group ( n = 776). The AOR of ASD and maternal obesity was 1.37 (95%CI 0.98–1.92). Associations with higher GWG were stronger (Quintile5 vs. Quintile3 AOR = 1.58, 95%CI 1.08–2.31), and particularly so among overweight/obese women (AOR = 1.90, 95%CI 0.98–3.68). DD was associated with maternal overweight and obesity (obesity AOR = 1.48, 95%CI 1.08–2.02), but not with total GWG or clinical recommendations. High maternal BMI and GWG are risk factors for other pregnancy and child outcomes, and our results suggest they may also represent modifiable risk factors for neurodevelopmental outcomes. Autism Res 2019, 12: 316–327 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In a large, national study, we found that children with autism were more likely than unaffected children to have mothers with higher weight gain during pregnancy; risk of autism may be even stronger if mothers were also overweight before pregnancy. Children with other developmental delays were more likely to have mothers who were overweight or obese before pregnancy, but not who gained more weight during pregnancy. Overweight and weight gain may represent factors that could be modified.